The author’s personal psychological experience in assessing the theatre work - Orlova, Tatiana D. (Journal of the Belarusian State University. Journalism, 2022)
The article deals with the psychological aspects of such an area of journalistic creativity as theatre criticism. The personal psychological experience of the author plays an important role in the evaluation of theatrical works. The features of the interpersonal and intergroup influence of the critic on the consciousness and behaviour of the audience are determined. The presence of practical and scientific professional knowledge when writing reviews is analysed, the content component of the personal psychological experience of a journalist-critic is highlighted. Distinguishing parameters between theatre criticism and theatre journalism are determined. The objective reasons for the transformation of theatre criticism are considered. The features of the personal manifestation of journalistic critical thinking are revealed.